Radiation reflection between face-to-face facades - Lim, Eugene JingYi (2014)
This paper presents an experimental study on the effects of cool coatings, as well as parameters like distance and orientation on the radiation reflected between the facades of two buildings. The effects of the parameters on the surface temperature of the two facades would also be discussed in order to provide a more comprehensive coverage of the study.